Oral Hypoglycaemic Effect of Canthium coromandelicum Leaf Extract on Wistar Rats - Widanagamage, Rahal; Ekanayake, Sagarika (My University, 2009)
Canthium coromandelicum (Burm. F), are trees found in dry scrub and monsoon forests in Sri Lanka and Southern India. Immature leaves have been a traditional food accompaniment to rice among the people living in Sri Lanka where the plant is frequently found. The present study was designed to investigate the possible oral hypoglycaemic activity of the leaf extract in rats. Percentage decreases of serum glucose levels of 15.4 % - 25.7 % were observed at doses of 15-30 g/ kg body weight following a glucose challenge. This is indicative of acute hypoglycaemic (anti-hyperglycaemic) activity of the leaf extract. Oral glucose challenge on the 8th and 15th day following repeated administration of leaf extract (20g/kg body weight) for 7 and 14 days did not suppress the fasting or the post-prandial serum glucose levels. It is concluded that the observed acute hypoglycaemic (anti-hyperglycaemic) effect is possibly due to inhibition or reduction of intestinal glucose absorption mediated by soluble dietary fibre (SDF; 1.2% DM) and pectin (38% of SO F) in the leaf. This will explain the absence of a chronic effect. This study provides evidence for its traditional recommendation as a functional food in diabetes.
Keywords: Canthium coromandelicum; Antihyperglycaemic activity; Normoglycaemic rats; Aqueous extract